The Impact of Body Mass Index on the Initial In-Brace Correction in Patients With Idiopathic Scoliosis - Pjanić, Samra; Talić, Goran; Bojinović-Rodić, Dragana (Scripta Medica, 2021)
Background/Aim: Many factors affect initial in-brace correction and treatment outcome in patients with idiopathic scoliosis. Previous studies have observed contradictory results on the role of BMI in orthotic treatment. The aim of this study was to examine whether BMI impacts in-brace correction, isolated and in relation to other predictive factors (curve magnitude, curve location and Risser sign). Methods: A retrospective study has been conducted on patients with idiopathic scoliosis treated with Cheneau-Sobernheim brace, that had no prior treatment. The collected and analysed data included patient demographics, BMI percentile and radiological parameters (curve magnitude in Cobb angle, curve location, Risser sign). The initial in-brace correction was expressed as a percentage of Cobb angle reduction in the brace as opposed to Cobb angle out of brace. Patients were categorised into groups according to their BMI, expressed in percentiles, ie: low BMI (< 5 percentiles), normal BMI (5-85 percentiles) and high BMI (> 85 percentiles). To determine the significant difference and correlation relationship between the examined variables, variance tests, t-test with unequal variance, and Pearson correlation coefficient have been used. Results: The cohort study comprised 213 patients (170 females and 43 males) with a mean age of 13.5 years at brace prescription. Low BMI has been detected in 10 % patients, normal BMI in 78 % and high BMI in 10 % patients. No significant difference in in-brace correction has been found between BMI groups, nor has there been any significant correlation between BMI and in-brace correction. Regarding other factors, significant difference within BMI groups was found between in-brace correction and curve location, as well as in-brace correction and Risser sign. Lumbar curves had significantly better in-brace correction than thoracic curves. Significant correlations between in-brace correction and curve magnitude, curve location and Risser sign were detected. Conclusion: The results of the present study show that, as an independent factor, BMI does not impact in-brace correction. Other factors, such as curve magnitude, curve location and Risser sign, play a more significant role in the orthotic treatment of patients with idiopathic scoliosis.